Second Five Year Plan (1956-57 to 1960-61) Thana District Bombay State - Planning Commission (Planning Commission, 1958)
Thana District covers an area of 3,729 sq. Miles, It is bounded on the North by the Portuguese territory of Daman and Surat District, on the East by Western Ghats, on the South by the Kolaba and Bombay Suburban Districts and on the West by the Arabian Sea. the District has been divided for administrative purpose into eleven Talukas and one Mahal. There arc three revenue divisions viz. Bhiwandi, Thana and Dahanu. Physical Features. This District consists of a distinct strip of low lands intersected by hilly tracts, rising to elevations varying from 100 to 2500 feet.
Bombay State